A proof‐of‐concept of parallel single‐drop microextraction for the rapid and sensitive biomonitoring of pesticides in urine - Mafra, Gabriela; Will, Camila; Huelsmann, Ricardo; Merib, Josias; Carasek, Eduardo (Journal of separation science, 2021)
In this study, a lab‐made parallel single‐drop microextraction methodology using the magnetic ionic liquid trihexyltetradecylphosphonium tetrachloromanganate (II) as extraction solvent was developed to determine the pesticides tebuconazole, pendimethalin, dichlorodiphenyltrichloroethane, and dichlorodiphenyldichloroethylene in human urine samples. The experimental setup consisted of a 96‐well plate system containing a set of magnetic pins that allowed for the manipulation of up to 96 samples simultaneously, providing an enhanced drop stability compared to traditional single‐drop microextraction approaches. The optimal conditions employed 5.38 ± 0.55 mg of extraction solvent, 1.5 mL of diluted urine samples (1:10), extraction time of 130 min, and subsequent dilution in 20 μL of acetonitrile. The method exhibited satisfactory analytical performance, with limits of detection of 7.5 μg/L for all analytes and coefficients of determination higher than 0.9955. Intraday and interday precisions ranged from 3 to 17% (n = 3) and 15 to 18% (n = 9), respectively, with relative recovery of analytes ranging from 70 to 122%. The method proposed was successfully applied in two human urine samples and no sign of the analytes was detected. The results demonstrated that the proposed method allowed for cost‐effective and high‐throughput methodology to be explored as a valuable tool in bioanalytical applications.